Poland - Public Expenditure Review : Analysis of Social Sectors and Public Wages - World Bank (World Bank, 2012)
This report looks at public spending on pensions, education, health, social assistance, labor market programs, and public wages. Presenting the findings of a series of studies and notes compiled sice April 2009, it highlights how reforming such spending, which comprises about one quarter of gross domestic product (GDP), is essential for mitigating the impact of the economic crisis and for transforming Poland from a welfare state to a workfare society in line with Government's Vision 2030. The report has two main messages. First, Poland can take measures to reduce public expenditures on social sectors and public wages by around 2.3 percentage points over the next three years. Second, beyond supporting the fiscal adjustment required in the context of the economic crisis, public expenditure reforms can also help bring about structural changes envisioned as part of the Government's strategy for 2030. This report provides a comprehensive assessment of Poland's social sector and public wage polices and lays out options for reform. The summary report has five parts. The first part lays out the macroeconomic context. It emphasizes that Poland has weathered the global economic crisis remarkably well but that the recovery is likely to be feeble and subject to uncertainty. The next part discusses the fiscal fallout of the crisis and argues that public expenditure reform should be a crucial pillar for fiscal consolidation. Sections three to five contain the main findings of the report. Section three presents a list of important reforms of public expenditures on social sectors and wages in support of Vision 2030. Section four simulates the fiscal impact of public expenditure reforms, with a particular focus on state budget expenditures. The final section discusses how institutional reforms in the areas of medium-term and performance-based budget can support the reform agenda. Volume two presents the detailed analyses of social sectors and institutional reforms of public finance.